EFFICACY AND SAFETY OF ELRANATAMAB IN PATIENTS WITH RELAPSED OR REFRACTORY MULTIPLE MYELOMA AND PRIOR B-CELL MATURATION ANTIGEN–DIRECTED THERAPIES: A POOLED ANALYSIS FROM MAGNETISMM STUDIES - A Nooka; A Lesokhin; M Mohty; R Niesvizky; C Maisel; B Arnulf; S Larson; A Varshavsky-Yanovsky; X Leleu; L Karlin; D Vesole; N Bahlis; et al. (Hematology, Transfusion and Cell Therapy, 2023)
Introduction/Objectives: To evaluate the efficacy and safety of elranatamab in a pooled analysis of patients (pts) enrolled in MagnetisMM trials with relapsed or refractory multiple myeloma (RRMM) who had prior exposure to B-cell maturation antigen (BCMA)-directed therapy. Materials and methods: Eligible pts received at least 1 proteasome inhibitor, 1 immunomodulatory drug, 1 anti-CD38 antibody, and 1 BCMA-directed therapy (antibody-drug conjugate [ADC] and/or chimeric antigen receptor [CAR]-T cells). The pooled analysis included pts in the MagnetisMM-1 trial (NCT03269136; n = 13) who received subcutaneous (SC) elranatamab 215-1000 μg/kg; MM-3 (NCT04649359; n = 64) and MM-9 (NCT05014412; n = 9) who received the recommended phase 2 dose of 76 mg SC once-weekly. Efficacy endpoints were evaluated by investigator per IMWG criteria. TEAEs were graded by CTCAE (MM-1, v4.03; MM-3 & MM-9, v5.0); CRS and ICANS were graded by ASTCT criteria. Results include data up through ≍10 months after last pt initial dose in all pooled studies. Results: In total, 86 pts were included. Median age was 66.0 y (range, 40-84); 47.7% male. At baseline, 69.8% had an ECOG PS ≥1; 24.4% had high risk cytogenetics; 54.7% had extramedullary disease. Pts received a median of 7.0 (3-19) prior lines of therapy, including BCMA-directed ADC (67.4%), CAR T-cells (41.9%); 9.3% received both. 96.5% and 54.7% of pts were triple-class and penta-drug refractory, respectively; among pts who received ADC and CAR-T cells respectively, 79.3% and 27.8% were refractory to ADC and CAR-T cells. After a median follow-up of 10.3 mo (0.3-32.3), median duration of treatment was 3.3 mo (0.03-30.4). At the cut-off date, 24.4% of pts remained on treatment; most common reason for permanent treatment discontinuation was progressive disease (44.2%). The overall response rate (ORR) was 45.3% (95% CI 34.6-56.5), with ≥CR achieved in 17.4% of pts. ORR for pts with prior BCMA-directed ADC and CAR-T cells was 41.4% (95% CI 28.6-55.1) and 52.8% (95% CI 35.5-69.6), respectively. Among responders, median time to objective response was 1.9 mo (0.3-9.3). Median duration of response (DOR) was not reached by 10 mo; the DOR rate at 9 mo was 72.4% (95% CI 54.7-84.2). DOR rate (95% CI) for pts with prior BCMA-directed ADC and CAR-T cells were 67.3% (43.1-83.0) and 78.9% (53.2-91.5) at 9 mo, respectively. Median progression-free survival was 4.8 mo (95% CI 1.9-7.7); median overall survival was not reached by 10 mo, with a rate of 60.1% (95% CI 48.9-69.6) at 9 mo. Most common (≥25% of pts) TEAEs were CRS (65.1% [G3 1.2%]), anemia (59.3% [G3/4, 46.5%]), neutropenia (44.2% [G3/4, 40.7%]), thrombocytopenia (40.7% [G3/4, 29.1%]), diarrhea (33.7% [G3/4, 0%], and lymphopenia (32.6% [G3/4, 30.2%]). 5.8% (G3, 2.3%) of pts. Discussion: In pts with RRMM and prior exposure to BCMA-directed therapies, elranatamab was efficacious and well tolerated; no new safety signals were observed vs the BCMA-naïve population. Conclusions: These results support treatment with elranatamab in pts with RRMM post BCMA-directed therapy.